Substance use and mental health disorders are linked to different forms of intimate partner violence victimisation. (1st June 2015) - Salom, Caroline L.; Williams, Gail M.; Najman, Jakob M.; Alati, Rosa
Highlights: We address links between mental health/substance disorders and intimate partner abuse. We account for experience of multiple intimate partner violence (IPV) forms. AUD are associated with psychological IPV victimisation; SUD with physical forms. Mental health disorders are associated with all forms of IPV experienced. Comorbid disorders increase the likelihood of psychological and physical forms of IPV. Abstract: Background: Substance and mental health disorders convey significant health burdens and impair interpersonal relationships. We tested associations between comorbid substance and mental health disorders and different forms of intimate partner violence (IPV) experienced by young adults. Method: Mothers ( n  = 6703) were recruited during pregnancy to the longitudinal Mater-University of Queensland Study of Pregnancy. Mother/offspring dyads were followed up from birth to 21 years. Offspring with complete psychiatric data at 21 years who reported having had an intimate partnership were included ( n  = 1781). Participants' experiences of psychological, physical and severe combined IPV were assessed at 21 years using a summarised form of the Composite Abuse Scale. We used the Composite International Diagnostic Interview to obtain lifetime diagnoses of mental health and substance disorders. Multivariable logistic regression models of each IPV form were adjusted for individual, family and neighbourhood factors during adolescence, and for other forms of IPV. Results: We have shown specific links between different forms of IPV experienced and individual substance and mental health disorders. Mental health disorders were related to all three forms of IPV, while alcohol disorders were linked to psychological IPV (ORAUD  = 1.86; 1.21–2.86) and illicit substance disorders to physical IPV (ORSUD  = 2.07; 1.25–3.43). The co-occurrence of related disorders was strongly linked to psychological and physical IPV. Conclusions: Intimate partner violence was experienced by both men and women. Substance and mental health disorders were associated with specific forms of IPV victimisation, suggesting that screening IPV clients and mental health/substance disorder patients for the converse problems may be important for intervention planning.